PERFORMANCE ANALYSIS OF MEDIATORS IN INDUSTRIAL RELATIONS PROBLEM SETTLEMENT PROCESS IN INDUSTRIAL AND MANPOWER OFFICES IN BADUNG REGENCY - Cahyadiputra, Made Krisna; Ayu Titha Paramita Pika, Putu (LPPM Univ. Ibn Khaldun Bogor, 2022)
This FieldWork Practice Report was made as an illustration of the results of the work that has been carried out during the PKL to meet one of the graduation requirements of students of the National University of Education (UNDIKNAS) Denpasar. The implementation of PKL as a medium to provide experience and provide broad knowledge related to the world of work, train mentally and discipline before entering the world of work. PKL activities are carried out at the Industrial and Manpower Office of Badung regency Jl. Raya Sempidi, Sempidi, Mengwi District, Badung Regency, Bali. Work Practices are carried out in the section of Industrial Relations and Worker Welfare. Fieldwork Practices are carried out for 2 (two) months starting from July 4, 2022, to September 2, 2022, with 5 working days, Monday – Thursday at 07.30 WITA to 15.30 WITA and Friday at 07:30 WITA to 12:00 WITA. The activities carried out practically during the PKL are: helping to complete the database in the form of a presentation chart me.